Pengetahuan dan Kesadaran Wajib Pajak orang pribadi terhadap Tingkat Kepatuhan Wajib Pajak orang pribadi dalam melaksanakan Kewajiban Perpajakan - Merliyana merliyana; Asep Saefurahman (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2017)
Some factors that can affect taxpayer compliance in fulfilling its tax obligations, including the knowledge and awareness of taxpayers against the provisions of taxation. Knowledge of the tax rules can be caused by the taxpayer's not understanding of the applicable tax law while taxpayer awareness is a factor that comes from within the taxpayer to fulfill his tax obligations sincerely and without coercion. Taxpayer awareness on the taxation function as state financing is necessary to improve taxpayer compliance. Low level of knowledge and awareness of taxpayers will affect taxpayer compliance in fulfilling its tax obligations, because taxpayers tend not to carry out their tax obligations or violate existing tax regulations. The purpose of research in writing this thesis, among others, to determine the effect of tax knowledge on taxpayer compliance level, to determine the effect of tax awareness on taxpayer compliance level and finally to know the influence of tax knowledge and tax awareness on taxpayer compliance level in East Jakarta Rawamangun area. This research uses survey type using quantitative approach which is calculated by using multiple linear regression method using SPSS 21.00 application. The population used in this study is an individual taxpayer who has income above PTKP by using the sample amount of 100 taxpayers. The data used in this study are primary and secondary data, with data collection methods using direct field observation techniques and literature study. The results of this study indicate the tax knowledge does not affect taxpayer compliance., Tax awareness does not affect taxpayer compliance and also shows the tax knowledge and tax awareness do not have an effect on taxpayer compliance.